2011
DOI: 10.1038/nchembio.551
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol modulates glycolipid conformation and receptor activity

Abstract: We document a new dimension of surface recognition in which communication is controlled through the collective behavior of lipids. Membrane cholesterol induces a tilt in glycolipid receptor headgroup, resulting in loss of access for ligand binding. This property appears to organize erythrocyte blood group presentation and glycolipid receptor function during the activation of sperm fertility, suggesting that lipid 'allostery' is a means to regulate membrane recognition processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
205
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(219 citation statements)
references
References 22 publications
13
205
1
Order By: Relevance
“…Due to the cross-reaction of anti-SSEA-3 antibody (MC-631) toward SSEA-4 and to a lesser extent, Gb4 (14), it is possible to overestimate the level of SSEA-3 detected by flow cytometry when there is a high expression level of SSEA-4. On the other hand, the level of SSEA-3 could be underestimated because of hindrance caused by other biomolecules on cell surface and thus SSEA-3 on the cells may not be reached in antibody staining (26,27). Therefore, we believe that the LC-MS result, which is supported by the qPCR detection of β3GalT5 gene expression (Fig.…”
Section: Cd24supporting
confidence: 50%
“…Due to the cross-reaction of anti-SSEA-3 antibody (MC-631) toward SSEA-4 and to a lesser extent, Gb4 (14), it is possible to overestimate the level of SSEA-3 detected by flow cytometry when there is a high expression level of SSEA-4. On the other hand, the level of SSEA-3 could be underestimated because of hindrance caused by other biomolecules on cell surface and thus SSEA-3 on the cells may not be reached in antibody staining (26,27). Therefore, we believe that the LC-MS result, which is supported by the qPCR detection of β3GalT5 gene expression (Fig.…”
Section: Cd24supporting
confidence: 50%
“…It is tempting to speculate that the moderate sensitivity of THP-1 cells toward Stx2 might be related to the 2.4 times higher cholesterol content and explicit accumulation of cholesterol in fractions F1-F3 in THP-1 cells when compared with Raji cells. Cell surface recognition seems to be controlled through the collective behavior of lipids, particularly by membrane cholesterol, which has been demonstrated to cause substantial loss of access for Stx to its GSL receptors ( 102,103 ). The high cholesterol content in THP-1 cell DRM fractions would support this hypothesis, although GSL-GSL interaction of monohexosylceramides (which are highly abundant in THP-1 cells) with Gb3Cer can counter cholesterol masking of Gb3Cer ( 102 ).…”
Section: Discussionmentioning
confidence: 61%
“…The activity of an OM efflux protein might potentially be impaired by altered diffusivity or defective gating associated with a change in membrane order (52). For instance, it has been shown that the substrate affinity of proteins and receptors in the eukaryotic plasma membrane is modulated by cholesterol ordering (35,56). Given the architectural convergence between the bacterial OM and the eukaryotic plasma membrane, similar mechanisms could account for the functional role of hopanoids in bacteria.…”
Section: Discussionmentioning
confidence: 99%